2014
DOI: 10.4236/as.2014.513138
|View full text |Cite
|
Sign up to set email alerts
|

Heifer Body Weight Gain and Reproductive Achievement in Response to Protein and Energy Supplementation While Grazing Dormant Range Forage

Abstract: Heifers grazing winter range require supplemental nutrients to complement dormant forage to achieve optimal growth and performance. A study was conducted to evaluate nutritional environment and effect of different supplementation strategies for developing heifers grazing dormant winter range. Eighty-four Angus crossbred heifers were stratified by body weight at weaning, allocated to one of six replicated pastures, and randomly assigned one of three supplemental treatments: 1) 908 g/d of a control supplement pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, Endecott et al (2013) suggests changes in mature BW have occurred over the decades and the recommendation for heifer target BW before breeding of 60% to 65% of mature weight may be different today than when first reported. Recent studies have shown that developing heifers to a lighter targeted BW of 50% to 57% allowed for reductions in heifer development costs and acceptable reproductive performance (Roberts et al, 2009a;Mulliniks et al, 2013;Waterman et al, 2014). The question then arises; how is first parity lactation impacted by this change in growth curve of heifers developed at BW <60% of mature BW?…”
Section: Resultsmentioning
confidence: 99%
“…However, Endecott et al (2013) suggests changes in mature BW have occurred over the decades and the recommendation for heifer target BW before breeding of 60% to 65% of mature weight may be different today than when first reported. Recent studies have shown that developing heifers to a lighter targeted BW of 50% to 57% allowed for reductions in heifer development costs and acceptable reproductive performance (Roberts et al, 2009a;Mulliniks et al, 2013;Waterman et al, 2014). The question then arises; how is first parity lactation impacted by this change in growth curve of heifers developed at BW <60% of mature BW?…”
Section: Resultsmentioning
confidence: 99%
“…In addition, RUP supplementation is recognized as a glucogenic source and responsible for increasing serum insulin levels (Table 6; Wiley et al, 1991;Waterman et al, 2006). Thus, the best performance for animals fed 51% of RUP may also be linked to a greater insulin sensitivity caused by this level of RUP inclusion (Waterman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%